2016
DOI: 10.2355/isijinternational.isijint-2015-428
|View full text |Cite
|
Sign up to set email alerts
|

Removing Tin from Tin-bearing Iron Concentrates with Sulfidation Roasting Using High Sulfur Coal

Abstract: With the sulfidation roasting process using high sulfur coal, the tin could be removed efficiently from tin-bearing iron concentrates, and the iron phase was reduced to metal iron. The research showed that the tin removal rate increased with roasting temperature and residence time. Different with the phenomena using pyrite as curing agent, deep reduction of tin-bearing concentrates did not cause tin remove rate decrease. The reason may be that curing rate of tin phases by the SO 2 generated from high sulfur co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…In the previous study, the tin could be effectively removed (Sn volatilization ratio > 90%) from tin-bearing iron concentrates by roasted with 70 wt.% sulfur-bearing stone coal under the conditions of N 2 atmosphere, roasting temperature of 1 200°C, residence time of 60 min and particle size minus 0.0750 mm. 10) The tin-bearing iron concentrate was firstly mixed with sulfur-bearing stone coal, grounded to minus 0.0750 mm, placed in a crucible, and then roasted in a tube furnace for a certain time under N 2 flow rate of 60 ml/min. It is difficult to determine the reactivity of sulfates in the sulfur-bearing stone coal for a low content.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous study, the tin could be effectively removed (Sn volatilization ratio > 90%) from tin-bearing iron concentrates by roasted with 70 wt.% sulfur-bearing stone coal under the conditions of N 2 atmosphere, roasting temperature of 1 200°C, residence time of 60 min and particle size minus 0.0750 mm. 10) The tin-bearing iron concentrate was firstly mixed with sulfur-bearing stone coal, grounded to minus 0.0750 mm, placed in a crucible, and then roasted in a tube furnace for a certain time under N 2 flow rate of 60 ml/min. It is difficult to determine the reactivity of sulfates in the sulfur-bearing stone coal for a low content.…”
Section: Methodsmentioning
confidence: 99%
“…4,[7][8][9] A method using sulfur-bearing stone coal to remove the excessive tin has been successfully performed on the laboratory level by the authors' group. 10) It is especially noteworthy that the Sn volatilization ratio has an obvious fluctuation with the variation of sulfur-bearing stone coal amount during the roasting process. In addition, previous studies have suggested that the sulfur occurs in inorganic and organic forms in sulfur-bearing stone coal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies shows iron and tin in the tin-bearing iron concentrates exist mainly in forms of magnetite (Fe 3 O 4 ) and cassiterite (SnO 2 ), and the Sn phase is almost embedded in the iron phase (Fe 3 O 4 ) at finegrained size, resulting that recovery of tin is low by mineral processing methods [6]. The tin could be separated efficiently through the methods of reduction or sulfidation roasting processes [6][7][8][9][10][11][12][13][14][15][16]. Reductant is used in many metallurgical processes to control oxygen potential of the reaction system [17].…”
Section: Introductionmentioning
confidence: 99%
“…Using CO as the reductant, for the reduction roasting process, the Sn phase (SnO 2 ) is reduced and further removed in the form of gaseous SnO, through which the tin content in the iron concentrate can decrease to 0.08 wt.% with the original tin content being below 0.35 wt.% in the tin-bearing iron concentrates [11][12]. The sulfidation roasting process takes place at a higher rate at the point of Sn removal than the reduction roasting process when the Sn content in the tin-bearing iron concentrate is relatively high, in which the tin volatilization rate reaches over 90% using the FeS 2 or high sulfur coal [8][9]. In this process, the SnO 2 is reduced firstly and then sulfurized and removed by gaseous SnS.…”
Section: Introductionmentioning
confidence: 99%